A hybrid method for a countable family of multivalued maps, equilibrium problems, and variational inequality problems - Suthep Suantai (2018)
We introduce a new monotone hybrid iterative scheme for finding a common element of the set of common fixed points of a countable family of nonexpansive multivalued maps, the set of solutions of variational inequality problem, and the set of the solutions of the equilibrium problem in a Hilbert space. Strong convergence theorems of the purposed iteration are established. Copyright © 2010 W. Cholamjiak and S. Suantai.